Query Rewriting with Thesaurus-Based for Handling Semantic Heterogeneity in Database Integration - Nugroho, I Made Riyan Adi; Sentana, I Wayan Budi (Knowledge Engineering and Data Science, 2020)
Nowadays, studies on handling semantic heterogeneity still become a challenge for researcher. Several methods have been used to solve these problems, one of which is query rewriting, implemented by rewriting a query into the latest one by using the selected schema. Semantic query rewriting needs a framework in order to identify the connection through the data schema sources. This line is used as a basis for scheme selection. Also, ontology is a model which often be used in these specific cases. The lack of ontology becomes a significant problem that usually seen. Therefore, this paper will describe an alternative framework in order to identify the link of semantic, which assisted by thesaurus.